Introductory rural sociology - Chitambar, J. B. (New Age International (P) Limited, Publishers, 2015)
"A textbook in Rural Sociology can follow many approaches. It may describe or analyse rural people and rural society in a particular country or culture; it may focus on one aspect of rural life and study analytically; it may deal with the rural situation in terms of specific social problems; or it may study rural society from some other point of view. This book is introductory and foundational in its approach. Its purpose is to introduce students who have been hitherto exposed almost exclusively to the natural and biological sciences, to the social sciences and specifically to Rural Sociology. It is addressed particularly to under-graduates and graduates of agriculture and related fields in India and similar developing countries of the world who intend to work directly or indirectly with rural people for their development and consequently seek to gain insight and understanding of their behaviour. Such understanding is not possible without comprehension of what goes to make up the structure of rural life and its operation and of the development of a framework which serves to analyse rural life. As an introductory textbook in Rural Sociology, this writing attempts to present students with basic concepts and principles of Rural Sociology that serve as a foundation for understanding the behaviour of rural people. These concepts and principles represent a connected set of facts and axioms in reference to which the student may organise and orient his thinking, define situations and communicate his thoughts and attitudes in respect of rural people. In doing, so he would develop a frame of reference for Rural Sociology. Such understanding and development of a frame of reference is a pre-requisite for deeper study of various aspects of rural behaviour and rural society as a whole. The author has therefore confined this introductory book to these so as to provide this essential foundation. Having done this the author had intended to devote a section of this writing to practical application of the concepts and principles presented, to programmes of promoted change for rural development, but this must perforce of circumstance be left for a later volume. The focus of presentation of the subject so as to make for comprehension and appreciation of its practical utility is of particular significance and importance to agricultural education in a developing country predominantly agricultural such as India which is involved in plans and programmes of rural development. In India, as agricultural education was stepped up with a view to accelerating development in agricultural production and other areas of rural development, it soon became evident that technical knowledge and communicating skills had to be coupled with adequate knowledge and understanding of rural people themselves if an effective strategy to promote desirable change was to be planned and implemented among them. The study of Rural Sociology hence has become a required formal course of study for all college students of agriculture and related fields."--